ANALISIS PENGARUH PROMOSI DAN FASILITAS TERHADAP PENINGKATAN JUMLAH PENGUNJUNG PANTAI LAWATA KOTA BIMA - Jukarnaedin Jukarnaedin; Mukhlis Mukhlis (Jurnal Bina Bangsa Ekonomika, 2022)
This study aims to find out and analyze the influence of promotion and facilitation on the increase in the number of visitors to Lawata Bima City. This type of research is associative research using quantitative data and primary data sources. The research instruments used in the study were questionnaires on a likert scale. The population in this study is all visitors to Lawata Beach Bima City whose numbers are not known with certainty. The sample technique used in this study is an accidental sampling technique that is an individual who happens to be found or that can be found at the research site alone studied, therefore sampling is as many as 96 respondents using the formula slovin. Data collection techniques used are observation tests, questionnaires / questionnaires and library studies. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test.  The results showed that promotions and facilities had a partial and simultaneous significant effect on the number of visitors to Bima City Lawata Beach with a strong level of association